The Role of Liver Resection at the Time of Secondary Cytoreduction in Patients With Recurrent Ovarian Cancer. Issue 1 (1st January 2014) - Kolev, Valentin; Pereira, Elena B.; Schwartz, Myron; Sarpel, Umut; Roayaie, Sasan; Labow, Daniel; Momeni, Mazdak; Chuang, Linus; Dottino, Peter; Rahaman, Jamal; Zakashansky, Konstantin
Abstract : Objective: The aim of this study is to determine the role of liver metastatectomy in the morbidity and survival of patients with recurrent ovarian carcinoma. Methods: We retrospectively reviewed the records of all patients who had undergone hepatic resection for liver metastases from ovarian carcinoma at the time of cytoreductive surgery at our institution from 1988 to 2012. The Kaplan-Meier method was used for survival analysis. A total of 76 patients met the inclusion criteria and had undergone liver resection as part of cytoreductive surgery for ovarian carcinoma during the study period. Of these 76 patients, 27 underwent liver resection at the time of secondary cytoreduction, and these patients that are the focus of this analysis. Results: Median overall survival for the study group from the time of diagnosis to the last follow-up or death was 56 months (range, 12–249 months). Twenty died of the disease with an overall median survival of 12 months from the time of the liver resection (2–190 months), and 7 patients were alive with the disease at the time of the last follow-up. Based on Kaplan-Meier survival analysis, the factors associated with the longest survival after the liver resection (2–190 months) were the interval from the primary surgery of less than 24 months versus more than 24 months ( P = 0.044) and secondary cytoreduction to residual disease of less than 1 cm ( P = 0.014). Conclusions: Based on our analysis of a single institution's series of ovarian cancer patients with hepatic metastasis, liver resection is feasible and safe and should be considered as an option in selected patients at the time of secondary cytoreduction.